Cayetano Heredia (Times of a life) - Ego Aguirre Febres, Ernesto (1956)
Lima was dismayed when he learned that he had died a great doctor. Earlier, one day in March, gave his last public notary will. In San Miguel de Miraflores, where no mishap disturbed the peace of the village, pen Jose Selaya was recording it, look at the suspended Miguel Evaristo de los Rios, a successor to the Dean of the Faculty of Medicine, and the Priest Don Eduardo Alvarado, a close friend. A strong emotion due to associates shudder when Cayetano Heredia, former Protomédico of the Nation and founder and first dean of the San Fernando House, decided that shrouded the Franciscan habit and in the same convent that was educated, simply and without ceremony, her funeral was held.